The Role of Professional Ethics in the Implementation of Financial Management in Companies - Deni Sulistyo; Dewi Setiawati; Lila Nurdiana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze ethical violations in corporate financial management by analyzing several cases that have occurred in Indonesia. The role of professional ethics in the application of financial management is a field of finance which is a broad and dynamic field. This field directly influences the life of every person and organization concerned. Business ethics is the basis of ethics in the economy or in business and for all stakeholders to avoid deviating from the economy and achieving goals or seeking profit, so we must master economic, legal, ethical and moral perspectives to achieve the desired goals. The conclusion in this article is that efforts to overcome problems that exist in the organizational or corporate environment related to violations or fraud committed by employees and company leaders involved in them have not been properly organized and the examples of cases of violations stated above have not been followed up by authorities. The perpetrators are now rampant so that efforts to overcome the problem of ethical violations must be directed at increasing the sense of corporate responsibility towards society as a whole.